Analytical and experimental investigation into the thermal aspects of droplet impingement - Quero García, Manuel (Cranfield University, 2006)
The mechanics and heat transfer of droplet impact is studied in the range of parameters interest for Super-cooled Large Droplet icing. The investigation explores the development of the splash produced experimental and numerically. A Navier-Stokes solver has been developed in order to compare experiments and modelling. Heat transfer is included in the simulations making possible the analysis of the thermal history during the impact of a Super-cooled droplet into a warm and running thin water film. Also a theoretical and numerical study has been undertaken in order to simulate the first stages of ice formation on the critical surfaces of aircraft during the droplet impact under freezing conditions due to super-cooled icing. The parameters considered experimental and numerically are: • Droplet size: 100-700Jlm. • Droplet impact velocity: 18-80m/s. • Angles of impact: 70°,45° and 20°. • Airflow (droplet) temperature: 200 e and _lOoe. • Water film thicknesses: 150Jlm and 50Jlm. • Water film temperature: 15°e and lOoe. • Water film velocity: 5m/s. The simulations are compared to the experiments run under the same conditions. Results for the parameters at the early stages of the splash agree well but as the splash process continues there are more differences between the two sets of results.